A Study on Success Rate of Candlesticks When Trading in Major Commodity Like Crude Oil - Bhaskar, G. (International Journal For Research In Business, Management And Accounting, 2015)
A candlestick is a type of Charts used under Technical analysis. It conveys the same informationrepresented in bar charts, but are visually displayed differently. The Open, High, Low and Closeof the chosen trading period will be represented in a single candle. Historically, candlestick charts are the oldest form of charts that have been used for predictingprices of rice. During this era in Japan, Munehisa Homma became legendary by making afortune in the rice trade using candlestick analysis. He is said to have performed over 100consecutive winning trades with this method.